Patient's attitude, knowledge and concerns regarding anesthesia - Fiuna, Dr. Aminath (2013)
Objectives: To assess patient's understanding and knowledge of the anesthesiologists roles and responsibilities and to identify peri-operative fears and concerns which they might have about anesthesia. Method: This is a cross-sectional study involving an interviewer-administered questionnaire conducted on adult patients for a period of 1 2-months from 2012 to 2013. A validated questionnaire containing 25 questions designed to assess the patient's fears,perceptions and concerns was used. A 5-point Likert scale was used whereby patients rated their responses. A statistical analysis was conducted at the end. Results: A total of 1 03 patients participated in the validated study and their responses scored. It was noted that there were factors loaded for 4 dimensions. A new questionnaire was formulated and 11 0 patients were questioned and responses validated. It was noted in descriptive analysis that majority of patients (above 80%) knew the anesthesiologists professions and above 60% knew their duties. A minor 25.5% knew that anesthesiologists played a role in resuscitation, and even a smaller number (7.3%) that the anesthesiologist actively resuscitated the patient during operation, such as transfusing blood if needed and monitoring of the vital signs. It was noted 70.9% patients were concerned of not being served analgesia on time. This was the biggest concern faced. Closely related were having an impairment of judgment and being incoherent. It was also noted that the patient regarded the anesthesiologist as being experienced and qualified. They were highly regarded. Conclusion: In the present study many patients responded well, despite having no history of surgery. Routine pre-op visits have been proven to be immensely beneficial in many aspects. A more thorough address of concerns and pre-op fears could greatly dissuade any apprehension that the patients may have about anesthesia. It is noted that the anesthesiologist could explain her role and confide in the patient about anesthesia to help the transition from doubt. And explain that anesthesiologists play a larger role when it comes to resuscitation.